Patient Engagement in Health Management as a Mediator Between Perceived Risk and COVID-19 Related Distress in Patients With IBD: A Structural Equation Model - Castellini, Greta; Palamenghi, Lorenzo; Savarese, Mariarosaria; Barello, Serena; Leone, Salvatore; Previtali, Enrica; Armuzzi, Alessandro; Graffigna, Guendalina (Frontiers in Psychiatry, 2021)
Objective: This study aimed to evaluate the impact of the COVID-19 emergency on patients with IBD's psychological distress, understanding the role of patient engagement as a mediator. Methods: An online questionnaire was created, measuring perceived risk susceptibility toward COVID-19, perceived stress, and patient engagement. The questionnaire was distributed to a purposive sample of IBD patients who belonged to the Italian Association for patients with IBD (AMICI Onlus) in April 2020. Structural equation models were implemented. Results: The effect of the perceived risk susceptibility toward COVID-19 contagion on the perceived stress is fully mediated by patient engagement (β = 0.306, p < 0.001). Moreover, the patient engagement mitigates the perceived stress (β = −0.748, p < 0.001) in our sample of IBD patients, and it is negatively influenced by the perceived risk susceptibility toward COVID-19 (β = −0.410, p < 0.001). Conclusion: Patient engagement is the key factor that explains how the perceived risk susceptibility toward COVID-19 affects the perceived psychological distress in patients with IBD, underlining that the perceived risk of contagion increases their perceived level of stress through a decrease of patient engagement.